Elaboración de la guía turística del cantón Bolívar - Vélez Bravo, Gabriela Celeste (2013)
This research aims to disseminate tourism cantón Bolívar, through an instrument like the guidebook, which are essential to promote tourist destinations. For what its design is analyzed, considering its appeal and content, and the importance of attributes that influence the image and the choice of destination. Research carried out on a set of national guidelines and international destinations, provides information about the utility and satisfaction that this instrument provides tourist information. In field work 150 surveys were obtained personal visitors arriving from different points of entry to the canton Bolivar, as well as in areas of high tourist. The findings indicate that guides moderately satisfied information needs of tourists and, affect the image of the destinations where such guides incorporate attractive elements and content